Envenoming by the viperid snake Proatheris superciliaris: a case report - Valenta, Jiri; Stach, Zdenek; Fricova, Dagmar; Zak, Jaroslav; Balik, Martin (Toxicon, 2008)
Snake bites caused by viperid snakes of Atheris genus are extremely rare, envenoming of a bite of related viper Proatheris superciliaris was described only once in the literature. The present case study depicts the envenoming of a 57 years old Czech man, a private herpetologist, who was bitten to his finger. He developed painful local reaction, nausea, hematuria, hypertension, chest and lumbar pain. Coagulopathy and thrombocytopenia subsequently developed as well as acute renal failure, hepatic and lung lesion. Intensive care therapy was purely symptomatic and supportive as no antisera exists. Treatment included haemodialysis, substitution of fresh frozen plasma and platelets. Patient completely recovered during 1 month.
Keywords: uštknutí hadem; Animals; Blood Coagulation Disorders; jedy chřestýšů; Fingers; transfuze trombocytů; Viperidae; Renal Dialysis; akutní poškození ledvin; dialýza ledvin; výsledek terapie; lidé; Platelet Transfusion; Crotalid Venoms; Treatment Outcome; Male; trombocytopenie; koagulopatie; prsty ruky; lidé středního věku; zvířata; mužské pohlaví; Acute Kidney Injury; Snake Bites; Thrombocytopenia; Middle Aged; Humans